Multiple components of the A1 adenosine receptor-adenylate cyclase system are regulated in rat cerebral cortex by chronic caffeine ingestion. - Ramkumar, V (1988)
The effects of chronic caffeine on the A1 adenosine receptor-adenylate cyclase system of rat cerebral cortical membranes were studied. Caffeine treatment significantly increased the number of A1 adenosine receptors as determined with the A1 adenosine receptor antagonist radioligand [3H]xanthine amine congener (XAC). R-PIA (agonist) competition curves constructed with [3H]XAC were most appropriately described by a two affinity state model in control membranes with a KH of 2.1 +/- 0.8 and a KL of 404 +/- 330 nM with 50 +/- 4% of receptors in the high affinity state (%RH). In contrast, in membranes from treated animals, there was a marked shift towards the high affinity state. In three of seven animals all of the receptors were shifted to a unique high affinity state which was indistinguishable from the KH observed in membranes from control animals. In four of seven animals the %RH increased from 50 to 69% with KH and KL indistinguishable from the control values. Thus, the agonist specific high affinity form of the receptor was enhanced following caffeine treatment. Maximal inhibition of adenylate cyclase activity in cerebral cortical membranes by R-PIA (1 microM) was significantly increased by 28% following caffeine treatment, consistent with an increased coupling of receptor-Gi protein with adenylate cyclase. Importantly, the quantity of Gi (alpha i) in rat cerebral cortex, determined by pertussis toxin-mediated labeling, was also increased to 133% of control values by this treatment. Thus, multiple components and interactions of the A1 adenosine receptor-adenylate cyclase complex are regulated by caffeine. These changes are likely compensatory measures to offset blockade of A1 receptors in vivo by caffeine and lead to a sensitization of this inhibitory receptor system.